KOMPETENCJE POCZĄTKUJĄCEGO NAUCZYCIELA JĘZYKA ANGIELSKIEGO W ŚWIETLE MODELU KARDS B. KUMARAVADIVELU - Werbińska, Dorota (Neofilolog, 2019)
This article focuses on first-year English teachers’ competences from the perspective of teachers themselves. The point of reference is offered by B. Kumaravadivelu’s (2012) language teacher education KARDS model (KNOWING, ANALYSING, RECOGNIZING, DOING and SEEING), which is based on cognitive and social constructivism. Providing an answer to progressing economic and educational globalization, the model stresses the need for verification of what contemporary language teachers’ competences constitute, For this reason the study described in the article seeks to find out how the competences of first-year teachers, as seen by the teachers themselves, match the requirements suggested in the model.